2018
DOI: 10.1186/s12885-018-4452-0
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic ductal adenocarcinoma can be detected by analysis of volatile organic compounds (VOCs) in alveolar air

Abstract: BackgroundIn the last decade many studies showed that the exhaled breath of subjects suffering from several pathological conditions has a peculiar volatile organic compound (VOC) profile. The objective of the present work was to analyse the VOCs in alveolar air to build a diagnostic tool able to identify the presence of pancreatic ductal adenocarcinoma in patients with histologically confirmed disease.MethodsThe concentration of 92 compounds was measured in the end-tidal breath of 65 cases and 102 controls. VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 41 publications
(35 reference statements)
2
44
0
Order By: Relevance
“…Other non-invasive alternatives to blood have been investigated as mediums for early detection biomarker research, namely the increased concentration of volatile organic compounds (VOC) in exhaled air specific. A recent case-control study found raised levels of VOC in patients with pancreatic cancer compared to healthy controls with a sensitivity and specificity of 100% and 84% respectively[ 85 ]. This is another avenue of potential further study in the development of a non-invasive biomarker for pancreatic cancer.…”
Section: Biomarkers For Early Detectionmentioning
confidence: 99%
“…Other non-invasive alternatives to blood have been investigated as mediums for early detection biomarker research, namely the increased concentration of volatile organic compounds (VOC) in exhaled air specific. A recent case-control study found raised levels of VOC in patients with pancreatic cancer compared to healthy controls with a sensitivity and specificity of 100% and 84% respectively[ 85 ]. This is another avenue of potential further study in the development of a non-invasive biomarker for pancreatic cancer.…”
Section: Biomarkers For Early Detectionmentioning
confidence: 99%
“…For exhaled breath sampling, subjects were asked to make one deep exhalation inside a hand-device called a Bio-VOC breath sampler ® (Markes International Ltd. Rhondda Cynon Taff. UK), which is a special 250 mL air syringe able to avoid any re-breath phase, as previously described [ 17 , 21 ]. Through the syringe, the breathed air flows into a 20 mL glass vial with a wide-bordered opening, formerly sterilized and kept at 80 °C for at least 24 h to avoid the presence of environmental pollutants.…”
Section: Methodsmentioning
confidence: 99%
“…An AirSense Compact analyzer and a V&F autosampler (V&F Analyse- und Messtechnik GmbH. Absam, Austria) were used for analyzing the volatile compounds present in the samples, as previously described [ 17 , 64 , 65 ]. The AirSense Compact analyzer consists of a conventional electron impact MS and a highly sensitive ion molecule reaction mass spectrometer (corresponding to chemical ionization mass spectrometry).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength is the ionization process offering the possibility to reduce fragmentation caused by high energy electron impact ionization. IMR-MS approach has been recently applied for VOCs detection in breath samples resulting, in combination with statistical treatments, in an improved diagnostic accuracy of breath analysis for the detection of pancreatic ductal adenocarcinoma [74] and liver diseases such as alcoholic fatty liver disease (AFLD) and non-AFLD (NAFLD) and cirrhosis [75,76].…”
Section: Introductionmentioning
confidence: 99%